Epigenetic Regulation of Skin Development and Regeneration (Stem Cell Biology and Regenerative Medicine,, 2018)
This indispensable volume highlights recent studies identifying epigenetic mechanisms as essential regulators of skin development, stem cell activity and regeneration. Chapters are contributed by leading experts and promote the skin as an accessible model system for studying mechanisms that control organ development and regeneration. The timely discussions contained throughout are of broad relevance to other areas of biology and medicine and can help inform the development of novel therapeutics for skin disorders as well as new approaches to skin regeneration that target the epigenome. Part of the highly successful Stem Cells and Regenerative Medicine series, Epigenetic Regulation of Skin Development and Regeneration uncovers the fundamental significance of epigenetic mechanisms in skin development and regeneration, and emphasizes the development of new therapies for a number of skin disorders, such as pathological conditions of epidermal differentiation, pigmentation and carcinogenesis. At least six categories of researchers will find this book essential, including stem cell, developmental, hair follicle or molecular biologists, and gerontologists or clinical dermatologists. .